Priority setting in developing countries health care institutions: the case of a Ugandan hospital - Martin Douglas K; Kapiriri Lydia (BMC, 2006)
Abstract Background Because the demand for health services outstrips the available resources, priority setting is one of the most difficult issues faced by health policy makers, particularly those in developing countries. However, there is lack of literature that describes and evaluates priority setting in these contexts. The objective of this paper is to describe priority setting in a teaching hospital in Uganda and evaluate the description against an ethical framework for fair priority setting processes - Accountability for Reasonableness. Methods A case study in a 1,500 bed national referral hospital receiving 1,320 out patients per day and an average budget of US$ 13.5 million per year. We reviewed documents and carried out 70 in-depth interviews (14 health planners, 40 doctors, and 16 nurses working at the hospital). Interviews were recorded and transcribed. Data analysis employed the modified thematic approach to describe priority setting, and the description was evaluated using the four conditions of Accountability for Reasonableness: relevance, publicity, revisions and enforcement. Results Senior managers, guided by the hospital strategic plan make the hospital budget allocation decisions. Frontline practitioners expressed lack of knowledge of the process. Relevance: Priority is given according to a cluster of factors including need, emergencies and patient volume. However, surgical departments and departments whose leaders "make a lot of noise" are also prioritized. Publicity: Decisions, but not reasons, are publicized through general meetings and circulars, but this information does not always reach the frontline practitioners. Publicity to the general public was through ad hoc radio programs and to patients who directly ask. Revisions: There were no formal mechanisms for challenging the reasoning. Enforcement: There were no mechanisms to ensure adherence to the four conditions of a fair process. Conclusion Priority setting decisions at this hospital do not satisfy the conditions of fairness. To improve, the hospital should: (i) engage frontline practitioners, (ii) publicize the reasons for decisions both within the hospital and to the general public, and (iii) develop formal mechanisms for challenging the reasoning. In addition, capacity strengthening is required for senior managers who must accept responsibility for ensuring that the above three conditions are met.